Peningkatan Kualitas Hidup Desa Bukit Peninjauan I Melalui Program KKN Berbasis Masjid - Iim Fahimah; Ahmad Yamani; Fitri Kurnia Wulandari; Tazki Amalia (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
The community in Bukit Peninjauan I, Sukaraja District, faces challenges related to low participation in religious activities, limited financial literacy, and inadequate child education programs. This community service program, conducted under the mosque-based framework, aims to enhance the quality of life through a series of religious, educational, and social initiatives. The activities include Islamic New Year and National Children's Day celebrations, regular mosque cleaning, health and financial literacy campaigns, and educational outreach. The participatory approach involved collaboration with local residents, religious leaders, and educators. Data collection methods included observation, interviews, and documentation, analyzed through qualitative techniques. The findings indicate increased community engagement, improved financial literacy, and heightened environmental awareness. The program's success underscores the potential of mosque-based initiatives in driving holistic community development and addressing rural challenges. This study concludes that mosque-centered programs effectively foster community resilience and social cohesion in rural settings.